International society of sports nutrition position stand: nutrition and weight cut strategies for mixed martial arts and other combat sports - Anthony A. Ricci; Cassandra Evans; Charles Stull; Corey A. Peacock; Duncan N. French; Jeffery R. Stout; David H. Fukuda; Paul La Bounty; Douglas Kalman; Andrew J. Galpin; Jaime Tartar; Sarah Johnson; et al. (Journal of the International Society of Sports Nutrition)
Following an extensive literature review, the International Society of Sports Nutrition (ISSN) has developed an official position on nutritional and weight cut strategies for combat sports. The type of combat sport, length of the fight camp, and time between weigh-in and competition are factors influencing nutritional and weight cut strategies. The following 16 points constitute the Position Statement of the Society; the Research Committee has approved them. 1. Combat sports have differing weight categories, official weigh-in times, and competition frequencies, influencing the nutritional and weight cut strategies for training and competition. 2. As the duration of a combat match increases, >4 min, contribution of the aerobic system can rise to >70%, yet anaerobic alactic pathways and anaerobic glycolytic pathways support high-output bursts. 3. During the off camp/general preparation phase, athletes should maintain a weight ranging 12% to 15% above the weight division requirement. 4. Supplements including creatine, beta-alanine, beta-hydroxy-beta-methylbutyrate, and caffeine have been shown to enhance performance and/or recovery during preparation phases, competition, and post-competition. 5. During fight camp, strategic decreases in calorie intake are necessary for an efficient longitudinal weight descent. Individual caloric needs can be determined using indirect calorimetry or validated equations such as Mifflin St. Jeor or Cunningham. 6. Protein should be prioritized during longitudinal weight descents to preserve lean body mass, and the timely delivery of carbohydrates supports training demands. Macronutrients should not drop below the following: carbohydrates 3.0–4.0 g/kg, protein 1.2–2.0 g/kg, and fat 0.5 to 1.0 g/kg/day. 7. Suitable losses in body mass range from 6.7% at 72 h, 5.7% at 48 h, and 4.4% at 24 h, prior to weigh-in. 8. Sodium restriction and water loading are effective for inducing polyuria and acute water loss. 9. During fight week, water-bound glycogen stores can be depleted through exercise and carbohydrate restriction, facilitating a 1% to 2% loss in body mass, with equivalent losses from a low-fiber intake of <10 g/day for 4 days. 10. During fight week, acute water loss strategies, including sauna, hot water immersion, and mummy wraps, can be used effectively with appropriate supervision (optimally ~2–4% of body mass within 24 h of weigh-in). 11. Post-weigh-in, rapid weight gain strategies are utilized to recover lost body fluid/mass before competition with the intent of gaining a competitive advantage. 12. Oral rehydration solutions (1 to 1.5 liters/h) combined with a sodium range of 50–90 mmol/dL should take precedence immediately post-weigh-in. 13. Fast-acting carbohydrates at a tolerable rate of ≤ 60 g/h should follow oral rehydration solutions. Post weigh-in intake of fiber should be limited to avoid gastrointestinal distress. 14. Post-weigh-in carbohydrate intake at 8–12 g/kg may be appropriate for combat athletes that undertook significant glycogen depletion strategies during fight week. About 4–7 g/kg may be suitable for modest carbohydrate restriction. 15. Post weigh-in, rehydration/refueling protocols should aim to regain ≥10% of body mass to mitigate declines in performance and the negative effects of rapid weight loss. 16. The long-term effects of frequent weight cuts on health and performance are unknown, necessitating further research.